Effect of boundary conditions on residual stress in cold metal transfer-based wire arc additively manufactured steel components - Xiongfeng Ruan; Burak Karabulut; Scott MacDonald; Jelena Dobrić; Barbara Rossi (Materials & Design)
This research focusses on wire arc additive manufacturing (WAAM) of carbon steel components made of 3Dprint AM35 (grade S355) by cold metal transfer-based welding process. A finite element (FE) model is developed to simulate the deposition process, and the numerical results are rigorously validated against experimental measurements, demonstrating that the temperature, deformation, and stress fields developing during the additive process can be reproduced accurately. The sensitivity of the FE model to ambient temperature, element activation strategies, alignment errors of thermocouples and strain gauges, and the use of a sequentially coupled approach is analysed. The effect of boundary conditions on the longitudinal and transverse residual stress patterns is studied, revealing that they are highly sensitive to the bolt pretension forces and substrate joining methods. However, they redistribute in a similar manner after the removal of the substrate. Guidance is provided to monitor the residual stress distribution in the fabricated component.